Ministry of Health Covid-19 Education Dialogue Poster: Contextual Meaning - Ulya, Chafit; Asih, Lutfi Anggoro; Nafisah, Yumna; Nawaila, Muhammad Bello (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
This research is motivated by a need for more public knowledge in preventing and treating the Coronavirus. The aim of this research is to determine and explain the form of contextual discourse analysis in the Covid-19 educational dialogue poster uploaded to the Instagram account of the Ministry of Health of the Republic of Indonesia. Data collection techniques use document analysis. The sampling technique used was purposive sampling. Data validity uses triangulation theory. Data analysis uses flowing analysis. The results of this research show that the contextual discourse of posters can be analyzed using the principles of personal, locational, temporal, analogical, and inference interpretation.It is hoped that the research results can provide benefits from contextual discourse analysis in understanding the meaning of uploads of Covid-19 educational dialogue posters through contextual principles in understanding the message conveyed.Â